Los derechos de los pueblos y comunidades indígenas en el Ecuador - Guanoluisa-Almache, Francisco Alejo; Espinoza-Castro, María Belén; Rubio-Benavides, Solange (IUSTITIA SOCIALIS, 2021)
Los derechos de los pueblos y comunidades indígenas en el Ecuador